Workshop Penulisan Karya Sastra untuk Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Indonesia Se-Kabupaten Cirebon - Novi Siti Kussuji Indrastuti; Asef Saeful Anwar (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2019)
Musyawarah Guru Mata Pelajaran (MGMP) in Cirebon District can be said to be lagging behind in following the development of the discourse of literature and writing because it is the outermost region of West Java Province. In connection with this, the Community Service activities carried out by the Indonesian Language and Literature Study Program, UGM Faculty of Cultural Sciences aim to convey the process of writing literary works that are easy and effective, revealing ways of developing stories in literary writing, and encouraging the publication of literary works written by participants in print and online. The methods used in the implementation of this activity are exemplary presentation methods, discussion and question and answer, persuasion, and practice and participation. In this writing workshop, three main points were presented which were the core material of this activity, namely the process of writing literary works, the technique of developing stories, and the use of media publications.-------------------------------------------------------------------Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Indonesia SMP se-Kabupaten Cirebon dapat dikatakan tertinggal dalam mengikuti perkembangan wacana karya sastra dan penulisannya karena merupakan wilayah terluar Jawa Barat. Sehubungan dengan hal tersebut, kegiatan Pengabdian kepada Masyarakat yang dilakukan oleh Prodi Bahasa dan Sastra Indonesia, Fakultas Ilmu Budaya UGM bertujuan menyampaikan proses penulisan karya sastra yang mudah dan efektif, mengungkapkan cara pengembangan cerita dalam penulisan karya sastra, dan mendorong terpublikasikannya karya sastra yang ditulis para peserta dalam bentuk cetak ataupun daring.  Metode yang digunakan dalam pelaksanaan kegiatan ini adalah metode presentasi ekstemporan, diskusi dan tanya-jawab, persuasi, serta praktik dan partisipatif. Dalam workshop penulisan ini disampaikan tiga hal pokok yang menjadi inti materi kegiatan ini, yakni proses penulisan karya sastra, teknik pengembangan cerita, dan pemanfaatan media publikasi.